The worthy role of hepatic arterial infusion chemotherapy in combination with anti-programmed cell death protein 1 monoclonal antibody immunotherapy in advanced hepatocellular carcinoma - Ding, Yixin; Wang, Shasha; Qiu, Zhenkang; Zhu, Chunyang; Wang, Yan; Zhao, Shufen; Qiu, Wensheng; Wang, Kongjia; Lv, Jing; Qi, Weiwei (Frontiers in Immunology, 2023)
Systemic therapy remains the primary therapeutic approach for advanced hepatocellular carcinoma (HCC). Nonetheless, its efficacy in achieving control of intrahepatic lesions is constrained. Hepatic arterial infusion chemotherapy (HAIC) is a therapeutic approach that combines localized treatment with systemic antitumor effects, which aim is to effectively manage the progression of cancerous lesions within the liver, particularly in patients with portal vein tumor thrombosis (PVTT). Combining HAIC with anti-programmed cell death protein 1 (anti-PD-1) monoclonal antibody (mAb) immunotherapy is anticipated to emerge as a novel therapeutic approach aimed at augmenting the response inside the localized tumor site and achieving prolonged survival advantages. In order to assess the effectiveness, safety, and applicability of various therapeutic modalities and to address potential molecular mechanisms underlying the efficacy of HAIC-sensitizing immunotherapy, we reviewed the literature about the combination of HAIC with anti-PD-1 mAb therapies.